The Potency of Lysinibacillus Sp. in Carbon Fiber and Zinc Oxide Nanoparticles Mixture to Suppress Ralstonia Solanacearum in Vitro - Ifa Dwi LUTHFIANA; Hersanti HERSANTI; Fitri WIDIANTINI (Indonesia Strategic Sustainability, 2023)
Ralstonia solanacearum is the cause of bacterial wilt on many Solanaceous crops. Antagonistic bacterium can be used to biologically control the pathogen. Lysinibacillus sp. was proven to be able to control R. solanacearum. To formulate the biopesticide, beside the active ingredients, a carrier materials is needed. The carrier material used in this study was 5% of 80 mesh carbon fiber as the site for the bacteria to attach, and enriched with ZnO nanoparticles (ZnO Nps) as one of the plant micro nutrients. The objective of the study was to determine the concentration of ZnO Nps that is viable for Lysinibacillus sp. and able to suppress the in vitro growth of R. Solanacearum. The antagonism test was carried out by using the completely randomized design with 11 treatments and 3 repetitions. The results showed that the largest inhibition zone, 8,30 mm, was caused by the treatment ZLd (ZnO NPs 1000 ppm + Lysinibacillus) without carbon, and 2,12 mm in the treatment of ZLKa ( (ZnO NPs 250 ppm + Lysinibacillus + carbon fiber) with carbon.